Evaluation of the concentration of allergens from mites in fur and households dust of dogs with atopic dermatitis - de Assunção, Dévaki L.; de Farias, Marconi R.; Barbosa, Michelle C.R.; de Araújo Machado, Luiz H. [UNESP] (FapUNIFESP (SciELO), 2017)
This study evaluated the concentration of Der p 1, Der f 1 and Blo t 5 in the fur and households of 20 dogs with atopic dermatitis (AD) and 20 healthy dogs. The diagnosis of AD was clinical based on Favrot's criteria. Dust samples were collected with a domestic vacuum cleaner. For each site, 1m2 was vacuumed for 2 min. The samples were collected in separate filters, transferred into plastic containers, sealed and kept frozen until ELISA analysis. In the fur of atopic dogs the average concentration of Der p 1 was 0.25μg/g compared to 0.03μg/g in healthy dogs. In households with atopic dogs the highest concentrations of Der p 1 were found in carpets (2.18μg/g), followed by couches (1.53μg/g), beds (1.14μg/g), dogs' bed linen (0.64μg/g) and floors (0.14μg/g). The concentrations of Der p 1 on carpets, couches and beds were significantly higher than in atopic dogs' fur (p<0.05). There was no statistical difference when comparing the concentrations of Der f 1 and Blo t 5 in different environments of atopic dogs (p>0.05). The concentrations of Der p 1, Der f 1 and Blo t 5 were equivalent in atopic and non-atopic dog's households. Among the allergens studied, Der p 1 was the most commonly found, predominantly in carpets and couches.
Keywords: Allergens; Atopic dermatitis; Dogs; Fur; Household dust; Mites